Implementasi Pengomposan Dan Eco Enzyme Dalam Pengolahan Sampah Rumah Tangga Di Kelurahan Abianbase - Shinta Enggar Maharani; Ni Luh Putu Mahendra Dewi (Jurnal Ecocentrism, 2022)
Lack of public knowledge on waste sorting and processing waste from the source causes air, water, and soil pollution to be unavoidable. Pollution is also evident in the landfill itself, where the landfill is overloaded due to irregular waste disposal. Reflecting on the existing problems, the solution offered is a community assistance program to sort and process household waste using the 3R concept and programs for making compost and eco-enzymes, which can be used to fertilize vegetable crops in their respective homes. Counseling on health care and environmental sustainability is the initial activity to make people aware of the importance of protecting the environment. Furthermore, residents are trained and continue to be assisted to be able to sort and process household waste into things that are more useful and have economic value. It is hoped that this activity can continue in a sustainable manner so that residents can get positive results such as picking organic vegetables in their own gardens and reducing the cost of transporting waste. If the activities in Kelurahan Abianbase can continue to run well, then the Village can be used as a model for other areas, in terms of household waste management.